Clinical characteristics and outcome of COVID‐19 pneumonia in kidney transplant recipients in Razi hospital, Rasht, Iran. Issue 6 (2nd August 2020) - Monfared, Ali; Dashti‐Khavidaki, Simin; Jafari, Ramezan; Jafari, Atefeh; Ramezanzade, Elham; Lebadi, Mohamad‐Kazem; Haghdar‐Saheli, Yalda; Aghajanzadeh, Pegah; Khosravi, Masoud; Movassaghi, Ali; Taghvaye‐Masoumi, Hamidreza; Alavi Foumani, Ali
Abstract: Background: In late December 2019, a novel coronavirus SARS‐CoV‐2 started to spread around the world in different populations. Its clinical and laboratory characteristics and outcome in kidney transplant recipients are little known. Therefore, we describe 22 kidney transplant recipients with SARS‐CoV‐2–induced pneumonia. Methods: All kidney transplant recipients who referred to the Razi Hospital of Rasht with a diagnosis of SARS‐CoV‐2 infection from February 20 to 19th of April 2020 have been included in this observational study. Results: We present 22 cases of COVID‐19 in kidney transplant recipients (median age 52 years [interquartile range 40.75‐62.75 years]) and baseline eGFR 60 (mL/min/1.73 m 2 ) (44.75‐86.75). Patients complained of cough (72.7%), dyspnea (63.6%), fever (68.2%), and chill (72.7%) with greater prevalence. We decreased the dose of immunosuppression and started stress dose of intravenous hydrocortisone or equivalent oral prednisolone. Each patient received antiviral therapy based on the latest updated version of local protocol at the time of admission. CT scan findings in 90.9% of patients showed bilateral multifocal lesions. Acute kidney injury (AKI) was observed in 12 patients during hospitalization. Six patients died after a median of 12 days from admission (IQR, 1‐21). Conclusions: In this small observational study, we observed high AKI occurrence and mortality rate in kidney transplant recipients with COVID‐19.